Are Uniform Tariffs Optimal? - Amiti, Mary (IMF Working Papers; Working Paper ;, 2004)
This paper analyzes whether uniform tariffs give rise to the highest welfare compared with tariffs that either escalate or de-escalate along the value chain of production. We show that countries may be better off with de-escalating tariffs where tariff rates are higher on intermediate inputs and lower on final goods. The key point is that higher tariffs can encourage agglomeration of intermediate input suppliers and final goods producers in one country. With high tariffs on intermediate inputs, the benefits of close proximity to final goods producers may outweigh the benefits of locating according to comparative advantage, which is more likely when the share of intermediate inputs in producing final goods is high. De-escalating tariffs yield the highest welfare when the benefits of agglomeration are very high. These benefits of agglomeration accrue to both countries in the form of lower prices.